Managing the image of the social organization on the example of the sports club - Sławomir Kowalski (Nowoczesne Systemy Zarządzania, 2018)
The third sector is the civic sector, which consists of entities most often called NGOs, but in addition to this definition, there are also several names: social organizations, non-profit organizations, voluntary organizations, civic organizations. The purpose of this article is to show the role of image managing and the directions of sport clubs development. The article will be based on research conducted on sports fans in terms of their attitude to the clubs and the importance of their image in the decision to purchase services and sports products. In addition, model-based solutions for the influence of the image on the functioning of sports clubs and the influence of external factors on this image will be presented. For the harmonious development of a sports organization in the local community, it is necessary to have a positive image, and any negative image-related phenomena negatively affect the basic activity of the club. The basic hypothesis assumes that there are constant factors that are the core of the sports club’s image and image-related factors resulting from the current image management. The result is a partial image management model in a sports club.